Implementasi Media Pembelajaran Berbasis Slow Motion Terhadap Motivasi Belajar Materi Senam "Anak Indonesia Hebat" Pada Siswa SD Negeri 2 Majenang - Tri Restu Mugiasih; Advendi Kristiyandaru; Mochamad Ridwan (Jurnal Keolahragaan, 2025)
This study aims to describe the implementation of slow motion-based learning media and its impact on students’ learning motivation in the "Anak Indonesia Hebat" gymnastics material. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The research subjects consisted of a physical education teacher and fifth-grade students at SD Negeri Majenang. The results showed that the use of slow motion videos significantly improved students' movement comprehension, interest, and active engagement in learning gymnastics. The increase in learning motivation was evident through greater participation, self-confidence, and student enthusiasm. Slow motion media proved to be effective as a visual aid in teaching complex movements gradually and enjoyably.